Efeito do trabalho a frio prévio na microestrutura e na resistência à corrosão do aço inoxidável lean duplex UNS S32304 soldado pelo processo GMAW - Carla Soares Souza (2018)
Duplex stainless steels (AID) are characterized by a biphasic structure with approximately equal volumetric fractions of ferrite and austenite, which gives them high mechanical performance and high resistance to corrosion. The lean duplex stainless steel UNS S32304 presents lower cost compared to other AID, due to its lower Ni%, and has been widely used in substitution of 304 and 316L austenitic steels. However the performance of this steel can be impaired by the use of industrial processes such as mechanical forming, thermo-mechanical treatments and welding. In this work the impact of the prior cold work on the microstructure, the hardness and the corrosion resistance of the UNS S32304 steel welded by the Gas Metal Arc Welding (GMAW) process, with two different welding energies, was evaluated. Samples of the UNS S32304 only cold rolled steel, with 0%, 10%, 30% and 50% of thickness reduction, and cold rolled and welded with energies denominated I and II were characterized by MO, subjected to microhardness measurement and analyzed for corrosion resistance in 3.5% m/v NaCl solution by open circuit potential, electrochemical impedance spectroscopy and cyclic potentiodynamic polarization. The cold work applied to the UNS S32304 steel caused flattening of the ferrite and austenite bands, generation of deformed regions in the austenite and increase of the hardness of the material, which increased with increasing thickness reduction. The welding generated regions with differentiated microstructures in the welded joint: Fuzion Zone (FZ), Heat-Affected Zone (HAZ), a annealed region around HAZ and the base metal (MB) deformed by cold working. The HAZ of all the welded sets showed excessive ferritization and high Cr2N precipitation. The hardness was higher for FZ and lower for HAZ. The BM presented increase in hardness with increasing thickness reduction and decrease in hardness with the proximity of HAZ. The samples only cold rolled with 10% and 30% of thickness reduction presented improvement in the corrosion resistance, compared to the non-laminated sample (0%). For 50% reduction of thickness there was reduction of corrosion resistance. Welding worsened the corrosion resistance of samples with 10% and 30% thickness reduction. For the sample with 50% thickness reduction it improved the generalized corrosion resistance, but reduced pitting corrosion resistance. The higher welding energy promoted a worsening in the generalized corrosion resistance of welded assemblies. The resistance to pitting corrosion was worsened when the lowest welding energy was used